An integrated processing preparation process of elevator metal fittings
Patent Information
- Application Number
- CN202611082859.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-21
- Publication Date
- 2026-10-20
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] This invention relates to the field of metal pressure processing and precision forming technology, specifically to an integrated processing and manufacturing process for elevator metal parts. Background Technology
[0002] Elevator metal fittings typically include mounting plates, connecting seats, supports, and irregularly shaped structural parts with holes, folds, mounting surfaces, and mating surfaces. In existing processing and manufacturing processes, the most common method is to sequentially process steel plates, iron-based materials, or metal blanks through blanking, punching, cutting, bending, shaping, machining, welding, and surface finishing to complete the forming. For fittings with more complex local structures or large variations in thickness, there are also process routes that use pressing, injection molding, sintering, and fine finishing to produce blanks, and then perform finishing on holes, end faces, and assembly parts to meet the requirements of elevator fittings for structural integration and mass production.
[0003] As elevator components develop towards multi-hole, integrated, and irregular shapes, related components often contain mounting holes, mating holes, edge transition areas, and large planar areas on the same part. When processing such integrated structures, existing processes may result in differences in the stress state, flow state, or subsequent shrinkage state of different areas. This can easily affect the forming coordination between hole diameter, hole center distance, edge transition, and main body plane. Especially under conditions of complex contours and multiple features, minor deviations formed in local areas may continue to be transmitted during subsequent shaping or heat treatment, thereby affecting the consistency of the overall structure.
[0004] Furthermore, in the existing integrated processing and manufacturing process, the contact state between materials, the degree of interface stability, and the connection relationship between each stage have a direct impact on the surface state and overall structure retention of the final component. When the distribution of particles, matrix, or lubricating components in the forming system is not stable enough, the response of the surface area and the internal area in the subsequent evolution process is prone to be different, which makes it difficult to simultaneously achieve the desired surface roughness, local densification state, and surface shape retention effect. For elevator metal parts that need to balance hole position accuracy, surface condition, and overall flatness, there is still room for further optimization of the above issues.
[0005] To address this technical deficiency, a solution is proposed. Summary of the Invention
[0006] The purpose of this invention is to provide an integrated processing and manufacturing process for elevator metal parts, which solves the technical problem that the dimensional stability and complex structure forming performance of elevator parts in the integrated near-net-shape forming process need to be further improved in the prior art.
[0007] The objective of this invention can be achieved through the following technical solutions:
[0008] An integrated processing technology for elevator metal parts includes the following steps:
[0009] S1. Weigh out 3.6-4.4 parts of paraffin wax, 1.8-2.4 parts of polyethylene wax and 0.9-1.2 parts of zinc stearate by weight, add them to a mixer, heat and melt them, and stir until uniform. Then add 37-41 parts of load-bearing strengthening powder, continue stirring until uniform, and then add 3.6-4.4 parts of stabilizing and lubricating powder. Knead the mixture at 118-128℃ for 35-45 minutes. After post-processing, the integrated molding material for elevator parts is obtained.
[0010] S2. The integrated composite material of elevator parts is added to the barrel of the injection molding machine and heated and plasticized. After uniform plasticization, it is injected into the mold cavity for molding. The elevator parts blank is demolded to obtain the elevator parts blank. The elevator parts blank is then placed in a degreasing furnace for degreasing treatment, and then placed in a sintering furnace for sintering treatment. After sintering, it is cooled to room temperature, the sintered body is taken out, and it is shaped and mechanically finished to obtain the integrated molded part of the elevator parts.
[0011] Furthermore, in step S1, the post-processing includes: after kneading, pouring out the material while it is still hot and cooling it to room temperature, followed by coarse crushing and granulation to obtain an integrated molding material for elevator parts with a particle size of 1-3 mm.
[0012] Furthermore, in step S2, the heating and plasticizing temperature is 125-145℃, the plasticizing time is 3-8 min, the mold temperature is 35-55℃, the injection pressure is 70-110 MPa, and the holding time is 15-35 s; the degreasing treatment conditions are to heat to 320-420℃ at 1-3℃ / min under a nitrogen atmosphere and hold for 2-4 h; the sintering treatment conditions are to heat to 1080-1150℃ at 4-8℃ / min under a vacuum of less than 10 Pa and hold for 1-2 h.
[0013] Furthermore, the preparation method of the load-bearing strengthening powder is as follows: iron-based pre-alloyed porous powder and enhanced coating powder are added to a mixer and mixed. After being mixed evenly, the mixture is pressed into a blank. The blank is then placed in a vacuum sintering furnace, vacuumed to below 10 Pa, heated to 430-470℃ at 4-6℃ / min and held for 35-45 min, and then heated to 1000-1040℃ at 7-9℃ / min and held for 50-70 min. The load-bearing strengthening powder is obtained after post-treatment.
[0014] Furthermore, the ratio of the iron-based pre-alloyed porous powder to the enhanced coating powder is 32-38g:4.5-5.8g. The post-processing includes: cooling to room temperature under nitrogen after sintering, taking out the sintered body and crushing, granulating and passing it through a 180-220 mesh sieve to obtain the load-bearing reinforced powder.
[0015] Furthermore, the preparation method of the iron-based pre-alloyed porous powder is as follows: Ferric nitrate nonahydrate, chromium nitrate nonahydrate, nickel nitrate hexahydrate, ammonium molybdate tetrahydrate, copper nitrate trihydrate, and deionized water are added to a reaction vessel and stirred until uniformly dissolved. Citric acid is then added and stirring continues for 20-40 minutes. Ethylene glycol is then added, and the reaction vessel is heated to 85-90℃ and stirred for 2-4 hours. The resulting material is then dried at 115-125℃ for 10-14 hours, treated at 280-320℃ for 0.5-1.5 hours, then kept at 780-820℃ for 1.5-2.5 hours under a hydrogen atmosphere, and finally kept at 1050-1100℃ for 0.8-1.5 hours under a nitrogen atmosphere. The post-treatment yields the iron-based pre-alloyed porous powder.
[0016] Furthermore, the ratio of the amounts of ferric nitrate nonahydrate, chromium nitrate nonahydrate, nickel nitrate hexahydrate, ammonium molybdate tetrahydrate, copper nitrate trihydrate, deionized water, citric acid, and ethylene glycol is 185-230g:19-24g:6.2-7.8g:1.7-2.2g:3.5-4.5g:720-900mL:108-132g:48-62mL. The post-treatment includes: cooling to room temperature after heat preservation, lightly pulverizing the obtained material and passing it through a 180-220 mesh sieve to obtain iron-based pre-alloyed porous powder.
[0017] Furthermore, the preparation method of the enhanced coating powder is as follows: titanium dihydrogenide, boron carbide and 0.15-0.25 wt% of tris(hydroxymethyl)aminomethane aqueous solution are added to a reaction vessel and stirred. After stirring evenly, dopamine hydrochloride is added, and the mixture is kept at 25-30℃ and stirred for 5-7 hours. Boric acid is then added, and the reaction vessel is heated to 42-48℃ and stirred for 1.5-2.5 hours. After the reaction is completed, the filter cake is collected by filtration. The filter cake is washed with deionized water 1-2 times, and then placed in a drying oven at 55-65℃ for vacuum drying for 8-12 hours. After that, it is lightly pulverized and passed through a 180-220 mesh sieve to obtain the enhanced coating powder.
[0018] Furthermore, the ratio of titanium dihydrogen phosphate, boron carbide, 0.15-0.25wt% aqueous solution of tris(hydroxymethyl)aminomethane, dopamine hydrochloride, and boric acid is 3.2-4.2g:1.2-1.6g:180-220mL:0.35-0.48g:0.16-0.24g. The post-treatment includes: after the reaction is completed, filtering and collecting the filter cake, washing the filter cake with deionized water 1-2 times, placing it in a drying oven at 55-65℃ for vacuum drying for 8-12h, then lightly pulverizing and passing it through a 180-220 mesh sieve to obtain the enhanced coating powder.
[0019] Furthermore, the preparation method of the stabilized lubricating powder is as follows: hexagonal boron nitride, molybdenum disulfide and 12-18 wt% hydrogen peroxide aqueous solution are added to a reaction vessel and stirred. After stirring evenly, the reaction vessel is heated to 58-62℃ and stirred for 1.5-2.5 h. After filtering and collecting the solid, the solid and the composite modified liquid are added to the reaction vessel, and the reaction vessel is heated to 68-72℃ and stirred for 2.5-3.5 h. The stabilized lubricating powder is obtained by post-processing.
[0020] Furthermore, the ratio of the hexagonal boron nitride, molybdenum disulfide, 12-18wt% hydrogen peroxide aqueous solution, and composite modification solution is 1.7-2.2g:1.7-2.2g:70-95mL:80-100mL. The post-treatment includes: after the reaction is completed, filtering and collecting the filter cake, washing the filter cake once with anhydrous ethanol and once with deionized water, placing it in a drying oven at 75-85℃ for vacuum drying for 6-10h, then lightly pulverizing and passing it through a 250-320 mesh sieve to obtain the stabilized lubricating powder.
[0021] Furthermore, the preparation method of the composite modified liquid is as follows: γ-aminopropyltriethoxysilane, anhydrous ethanol, deionized water and glacial acetic acid are added to a reaction vessel and stirred for 30-40 min to obtain the composite modified liquid, wherein the ratio of γ-aminopropyltriethoxysilane, anhydrous ethanol, deionized water and glacial acetic acid is 0.18-0.26 mL:70-90 mL:18-25 mL:0.12-0.22 mL.
[0022] The present invention has the following beneficial effects:
[0023] 1. The load-bearing strengthening powder prepared in this invention constitutes the main load-bearing skeleton. Its internal iron-based continuous phase and the in-situ formed titanium-containing boride and titanium carbide are in the same structural unit. After entering the forming system, it can enable the component to maintain a relatively continuous shrinkage transfer relationship in the stages of filling, degreasing and sintering. Especially in the hole, edge and adjacent structural transition area, the continuous skeleton does not show a simple hard filling, but participates in the material flow transfer and interface adjustment together with the hexagonal boron nitride and molybdenum disulfide in the stabilized lubricating powder. This makes the transport process of the molten bonding phase in the complex contour more balanced. As a result, when the component transforms from the green body to the sintered body, the geometric correspondence between the assembly-related parts is more likely to be maintained along the same evolution path, and the local area and the overall contour also show good synergy.
[0024] 2. The configuration of the stabilized lubricating powder prepared by this invention in the system has a more direct impact on the formation of the surface structure. Hexagonal boron nitride and molybdenum disulfide are dispersed in the molding material after surface stabilization. During the mixing, plasticizing and injection stages, they play a continuous role in regulating the material flow state near the mold cavity surface, making it less likely for particle dragging, local stagnation or flow marks to accumulate on the surface. At the same time, the iron-based continuous phase in the load-bearing strengthening powder provides stable support for the surface. The titanium-containing boride and titanium carbide present in situ maintain the continuity of the surface structure during subsequent heat treatment, avoiding obvious loosening or unevenness of the surface during the continuous degreasing and densification process. As a result, the morphological evolution between the main surface, the periphery area and the edge transition area can maintain a more natural connection, and the surface state is more likely to reflect the consistency that should be present under near-net-shape forming conditions.
[0025] 3. When the heat treatment enters the densification stage, the structural characteristics of the reinforcing powder begin to be more fully manifested. The internal iron-based continuous phase undertakes the overall connection function, and titanium boride and titanium carbide are distributed in situ, so that the shrinkage process of the reinforcing structure and the matrix is within the same thermal process, and the interface mismatch common to added particles is less likely to occur. The hexagonal boron nitride and molybdenum disulfide in the stabilizing lubricating powder are not separate from this process, but on the basis of the uniform distribution in the early stage, they form an auxiliary adjustment to the local interface state and stress release path. After the two work together, the plate surface, hole edge and edge tend to show a coordinated response during the continuous heating and shrinkage process. The overall structural integrity, surface shape maintenance state and subsequent service continuity are thus established with a smoother internal connection. Attached Figure Description
[0026] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0027] Figure 1 This is a SEM image of the load-bearing reinforced powder prepared in Example 3 of the present invention;
[0028] Figure 2 This is a SEM image of the stabilized lubricating powder prepared in Example 6 of the present invention;
[0029] Figure 3 This is a SEM image of the fracture surface of the integrated molded elevator component prepared in Example 6 of the present invention. Detailed Implementation
[0030] The technical solution of the present invention will be clearly and completely described below with reference to the embodiments. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0031] In this application, the purity of the hexagonal boron nitride used is 98.5-99.5 wt%, and the median particle size D50 is 5-6 μm; the melting point of the paraffin used is 60-62℃; and the dropping point of the polyethylene wax used is 104-108℃, and the number average molecular weight is 2500-2700.
[0032] Example 1
[0033] This embodiment provides a method for preparing load-bearing reinforced powder, including the following steps:
[0034] Step ①: Preparation of iron-based pre-alloyed porous powder
[0035] Weigh out 185.0g of ferric nitrate nonahydrate, 19.0g of chromium nitrate nonahydrate, 6.2g of nickel nitrate hexahydrate, 1.7g of ammonium molybdate tetrahydrate, 3.5g of copper nitrate trihydrate, and 720.0mL of deionized water and add them to the reaction vessel. Stir until dissolved and homogeneous. Then add 108.0g of citric acid and continue stirring for 20 minutes. Add 48.0mL of ethylene glycol and heat the reaction vessel to 85℃ and stir for 2 hours. Dry the resulting material at 115℃ for 10 hours, then treat it at 280℃ for 0.5 hours. Then keep it at 780℃ for 1.5 hours under a hydrogen atmosphere and at 1050℃ for 0.8 hours under a nitrogen atmosphere. After the heat treatment is completed, cool to room temperature, lightly pulverize the resulting material and pass it through a 180-mesh sieve to obtain iron-based pre-alloyed porous powder.
[0036] The reaction principle for preparing iron-based pre-alloyed porous powder is as follows:
[0037] Ferric nitrate nonahydrate, chromium nitrate nonahydrate, nickel nitrate hexahydrate, ammonium molybdate tetrahydrate, and copper nitrate trihydrate dissolve in water to form a homogeneous polymetallic salt solution. Upon addition of citric acid, the metal ions complex with the citric acid, reducing the tendency for different metal components to separate in the solution. After adding ethylene glycol and heating, the citric acid and ethylene glycol undergo condensation, promoting a more uniform distribution of the metal components within the organic gel system. During subsequent drying and heat treatment, the organic components gradually decompose and form mixed oxides. Under a hydrogen atmosphere, the relevant metal oxides are reduced. Further heating and holding under a nitrogen atmosphere leads to solid-phase diffusion and alloying of the metal components, ultimately yielding a relatively homogeneous iron-based pre-alloyed porous powder.
[0038] Step 2: Preparation of synergistic coating powder
[0039] Weigh out 3.2g of titanium dihydrogen phosphate, 1.2g of boron carbide and 180.0mL of 0.15wt% tris(hydroxymethyl)aminomethane aqueous solution and add them to the reaction vessel. Stir until uniform, then add 0.35g of dopamine hydrochloride and keep the mixture at 25℃ for 5h. Then add 0.16g of boric acid and heat the reaction vessel to 42℃ and keep it at 42℃ for 1.5h. After the reaction is complete, filter and collect the filter cake. Wash the filter cake once with deionized water and then place it in a drying oven at 55℃ for vacuum drying for 8h. Then lightly pulverize and pass it through a 180-mesh sieve to obtain the enhanced coating powder.
[0040] The reaction principle for preparing the enhanced coating powder is as follows:
[0041] Under the weakly alkaline conditions provided by the aqueous solution of tris(hydroxymethyl)aminomethane, dopamine in dopamine hydrochloride undergoes oxidative polymerization and gradually deposits on the surface of titanium dihydrogen phosphate and boron carbide particles to form an organic coating layer. Boric acid is then added, and the boric acid coordinates and esterifies with the catechol hydroxyl groups in the coating layer, further stabilizing the surface coating layer. In this process, titanium dihydrogen phosphate and boron carbide mainly exist as the coated solid particles, while dopamine completes the surface polymerization deposition. Boric acid is used to regulate and stabilize the coating layer structure, ultimately yielding an enhanced coated powder with a stable surface coating layer.
[0042] Step ③: Preparation of load-bearing reinforced powder
[0043] Weigh 32.0g of iron-based pre-alloyed porous powder and 4.5g of enhanced coating powder and add them to the mixer. After mixing evenly, press the mixture into a blank and place it in a vacuum sintering furnace. Evacuate the furnace to below 10Pa, heat it to 430℃ at 4℃ / min and hold for 35min, then heat it to 1000℃ at 7℃ / min and hold for 50min. After cooling, cool it to room temperature under nitrogen after sintering. Take out the sintered body and crush, granulate and pass it through a 180-mesh sieve to obtain the load-bearing reinforced powder.
[0044] The reaction principle for preparing load-bearing reinforced powder is as follows:
[0045] After the iron-based pre-alloyed porous powder and the enhanced coating powder are mixed and pressed into a blank, the powder is heated under vacuum conditions. The coating layer in the enhanced coating powder first undergoes thermal decomposition, and titanium dihydrogenate undergoes dehydrogenation decomposition as the temperature rises to generate metallic titanium. When the temperature continues to rise, metallic titanium reacts in situ with boron carbide to form a ceramic phase containing titanium boride and titanium carbide. At the same time, sintering bonding occurs between the iron-based pre-alloyed particles, and continuous metallurgical connection is gradually formed at the particle contact interface. The entire heat treatment process includes dehydrogenation, in-situ reaction and sintering densification processes, and finally, a load-bearing reinforced powder composed of iron-based phase and titanium-containing ceramic phase is obtained.
[0046] The mechanism of action of load-bearing strengthening powder in integrated molded elevator parts is as follows:
[0047] The load-bearing strengthening powder obtained by this process essentially constitutes the core load-bearing unit in the subsequent integrated molding system. Its interior is composed of an iron-based continuous phase and in-situ distributed titanium-containing borate and titanium carbide. The former provides the continuous connection foundation required in the subsequent molding and sintering process, while the latter is embedded in the continuous structure to form stable support and constraint for local areas. After entering the system, this type of composite load-bearing unit not only participates in the coating of binder components, material flow transfer and particle rearrangement, but also continues to affect the shrinkage response mode of different areas during the debinding and sintering stages. This makes it easier for the holes, edges and transition areas to maintain a coherent structural evolution relationship with the main body area, thereby establishing the internal load-bearing network, surface state and overall structural coordination of the final integrated molded elevator parts on a more stable structural foundation.
[0048] Example 2
[0049] This embodiment provides a method for preparing load-bearing reinforced powder, including the following steps:
[0050] Step ①: Preparation of iron-based pre-alloyed porous powder
[0051] Weigh out 230.0g of ferric nitrate nonahydrate, 24.0g of chromium nitrate nonahydrate, 7.8g of nickel nitrate hexahydrate, 2.2g of ammonium molybdate tetrahydrate, 4.5g of copper nitrate trihydrate, and 900.0mL of deionized water and add them to the reaction vessel. Stir until the mixture is evenly dissolved. Then add 132.0g of citric acid and continue stirring for 40 minutes. Next, add 62.0mL of ethylene glycol and heat the reaction vessel to 90℃. Keep the mixture at this temperature and stir for 4 hours. Dry the resulting material at 125℃ for 14 hours, then treat it at 320℃ for 1.5 hours. Then keep it at 820℃ for 2.5 hours under a hydrogen atmosphere and at 1100℃ for 1.5 hours under a nitrogen atmosphere. After the heating is completed, cool the material to room temperature, lightly pulverize it, and pass it through a 220-mesh sieve to obtain iron-based pre-alloyed porous powder.
[0052] Step 2: Preparation of synergistic coating powder
[0053] Weigh out 4.2g of titanium dihydrogen phosphate, 1.6g of boron carbide and 220.0mL of 0.25wt% tris(hydroxymethyl)aminomethane aqueous solution and add them to the reaction vessel. Stir until uniform, then add 0.48g of dopamine hydrochloride and keep the mixture at 30℃ for 7h. Then add 0.24g of boric acid and heat the reaction vessel to 48℃ and keep it at 48℃ for 2.5h. After the reaction is complete, filter and collect the filter cake. Wash the filter cake twice with deionized water and then place it in a drying oven at 65℃ for vacuum drying for 12h. Then lightly pulverize and pass it through a 220-mesh sieve to obtain the enhanced coating powder.
[0054] Step ③: Preparation of load-bearing reinforced powder
[0055] Weigh out 38.0g of iron-based pre-alloyed porous powder and 5.8g of enhanced coating powder and add them to the mixer. After mixing evenly, press the mixture into a billet and place it in a vacuum sintering furnace. Evacuate the furnace to below 10Pa and heat it to 470℃ at 6℃ / min for 45min. Then heat it to 1040℃ at 9℃ / min for 70min. After cooling, cool it to room temperature under nitrogen after sintering. Take out the sintered body and crush, granulate and pass it through a 220-mesh sieve to obtain the load-bearing reinforced powder.
[0056] Example 3
[0057] This embodiment provides a method for preparing load-bearing reinforced powder, including the following steps:
[0058] Step ①: Preparation of iron-based pre-alloyed porous powder
[0059] Weigh out 207.5g of ferric nitrate nonahydrate, 21.5g of chromium nitrate nonahydrate, 7.0g of nickel nitrate hexahydrate, 2.0g of ammonium molybdate tetrahydrate, 4.0g of copper nitrate trihydrate, and 810.0mL of deionized water and add them to a reaction vessel. Stir until the mixture is evenly dissolved. Then add 120.0g of citric acid and continue stirring for 30 minutes. Next, add 55.0mL of ethylene glycol and heat the reaction vessel to 88℃. Keep the temperature and stir for 3 hours. Dry the resulting material at 120℃ for 12 hours, then treat it at 300℃ for 1 hour. Then keep it at 800℃ for 2 hours under a hydrogen atmosphere and at 1075℃ for 1.2 hours under a nitrogen atmosphere. After the heating is completed, cool it to room temperature. Lightly pulverize the resulting material and pass it through a 200-mesh sieve to obtain iron-based pre-alloyed porous powder.
[0060] Step 2: Preparation of synergistic coating powder
[0061] Weigh out 3.7g of titanium dihydrogen phosphate, 1.4g of boron carbide, and 200.0mL of 0.20wt% tris(hydroxymethyl)aminomethane aqueous solution and add them to the reaction vessel. Stir until homogeneous, then add 0.42g of dopamine hydrochloride. Keep the mixture at 28℃ and stir for 6h. Then add 0.20g of boric acid and heat the reaction vessel to 45℃ and stir for 2.0h. After the reaction is complete, filter and collect the filter cake. Wash the filter cake twice with deionized water and then place it in a drying oven at 60℃ for vacuum drying for 10h. Finally, lightly pulverize and pass it through a 200-mesh sieve to obtain the enhanced coating powder.
[0062] Step ③: Preparation of load-bearing reinforced powder
[0063] Weigh 35.0g of iron-based pre-alloyed porous powder and 5.2g of enhanced coating powder and add them to a mixer to mix. After mixing evenly, press the mixture into a billet and place it in a vacuum sintering furnace. Evacuate the furnace to below 10Pa, raise the temperature to 450℃ at 5℃ / min and hold for 40min, then raise the temperature to 1020℃ at 8℃ / min and hold for 60min. After cooling, cool the sintered body to room temperature under nitrogen. Remove the sintered body and crush, granulate and pass it through a 200-mesh sieve to obtain the load-bearing reinforced powder.
[0064] Example 4
[0065] This embodiment provides an integrated processing and manufacturing process for elevator metal parts, including the following steps:
[0066] Step 1: Preparation of Stabilized Lubricating Powder
[0067] Weigh out 0.18 mL of γ-aminopropyltriethoxysilane, 70.0 mL of anhydrous ethanol, 18.0 mL of deionized water and 0.12 mL of glacial acetic acid and add them to the reaction vessel. Stir for 30 min to obtain the composite modified solution.
[0068] Weigh out 1.7g of hexagonal boron nitride, 1.7g of molybdenum disulfide, and 70.0mL of 12wt% hydrogen peroxide aqueous solution and add them to the reaction vessel. Stir until homogeneous, then heat the reaction vessel to 58℃ and stir for 1.5h. After filtering and collecting the solid, add the solid and 80.0mL of composite modification solution to the reaction vessel and heat the reaction vessel to 68℃ and stir for 2.5h. After the reaction is complete, filter and collect the filter cake. Wash the filter cake once with anhydrous ethanol and once with deionized water, then place it in a drying oven at 75℃ and vacuum dry for 6h. Finally, lightly pulverize and pass it through a 250-mesh sieve to obtain the stabilized lubricating powder.
[0069] The reaction principle for preparing stabilized lubricating powder is as follows:
[0070] γ-aminopropyltriethoxysilane undergoes hydrolysis in a system of ethanol, deionized water, and glacial acetic acid to generate an active component containing silanol groups. After hexagonal boron nitride and molybdenum disulfide are treated in an aqueous hydrogen peroxide solution, their surface states are activated. When the treated solid is added to a composite modification solution, the silane hydrolysis products bind to the particle surface on one hand and undergo condensation on the other, thus forming a relatively stable organosilicon modified layer on the surface of hexagonal boron nitride and molybdenum disulfide. This process mainly includes silane hydrolysis, particle surface activation, and surface condensation grafting, ultimately yielding a surface-modified stable lubricating powder.
[0071] The mechanism of action of stabilized lubricating powder in integrated molded elevator parts is as follows:
[0072] The stabilized lubricating powder obtained by this process essentially constitutes the interface adjustment unit in the subsequent integrated molding system. Its structural basis lies in the fact that hexagonal boron nitride and molybdenum disulfide, after surface stabilization, form an outer interface that is easier to distribute in synergy with the organic binder phase and the metal carrier phase. Thus, after entering the system, it does not simply exist as a lubricating filler, but continuously affects the contact state between particles, the coating mode of the binder components, and the material flow transmission path during the mixing, plasticizing, and injection stages, making the dispersion and migration of the carrier-reinforcing powder in complex contour areas more stable. Furthermore, this type of interface adjustment effect continues into the degreasing and sintering stages, making it easier for the surface area and the internal area to maintain continuous connection during the migration of organic components, local shrinkage, and structural rearrangement. As a result, the surface state, edge transition, and overall structural coordination of the final integrated elevator component are established on a more stable interface basis.
[0073] Step 2: Preparation of integrated molding material for elevator components
[0074] By weight, 3.6 parts of paraffin wax, 1.8 parts of polyethylene wax and 0.9 parts of zinc stearate were weighed and added to a mixer, heated and melted, and stirred. After stirring evenly, 37 parts of the load-bearing strengthening powder prepared in Example 1 were added, and after stirring evenly, 3.6 parts of the stabilizing lubricating powder were added. The mixture was kneaded at 118°C for 35 minutes. After kneading, the material was poured out while hot and cooled to room temperature. Then, it was coarsely crushed and granulated to obtain an integrated molding material for elevator parts with a particle size of 1 mm.
[0075] The reaction principle for preparing integrated molding materials for elevator components is as follows:
[0076] Paraffin wax, polyethylene wax, and zinc stearate are melted under heating conditions to form a continuous organic phase. After the load-bearing reinforcing powder is added, it is dispersed in the organic phase and achieves relatively uniform mixing during the mixing process. After the stabilizing lubricating powder is added, it is dispersed together with the aforementioned solid components in the melt bonding system. This step is mainly a process of melt mixing, coating and wetting, and uniform dispersion. Paraffin wax and polyethylene wax constitute the main bonding medium, zinc stearate plays an auxiliary role in dispersion and processing regulation, and the load-bearing reinforcing powder and stabilizing lubricating powder are stably introduced into the system as solid components, finally obtaining an integrated molding material for elevator parts suitable for subsequent molding.
[0077] Step 3: Fabrication of integrated molded elevator components
[0078] The integrated elevator component molding material is added to the injection molding machine barrel and heated and plasticized at a temperature of 125℃ for 3 minutes. The mold temperature is 35℃, the injection pressure is 70MPa, and the holding time is 15 seconds. After uniform plasticization, the material is injected into the mold cavity for molding. The molded part is then demolded to obtain an elevator component preform. The preform is then placed in a degreasing furnace and degreased at 320℃ under a nitrogen atmosphere at a rate of 1℃ / min for 2 hours. Subsequently, it is placed in a sintering furnace and sintered at 1080℃ under a vacuum of less than 10Pa at a rate of 4℃ / min for 1 hour. After sintering, the preform is cooled to room temperature, removed, and shaped and mechanically finished to obtain a rectangular plate with dimensions of 100mm×25mm×6mm. Two mounting holes with a diameter of Φ6.5mm and a center distance of 70mm are arranged along the length, and the ends are rounded with radius R2.
[0079] The reaction principle for manufacturing integrated elevator parts is as follows:
[0080] After being heated and plasticized in an injection molding machine, the binder component of the integrated elevator component molding material becomes a flowable state, thereby driving the solid powder into the mold cavity and forming the required preform. In the degreasing stage, organic components such as paraffin wax, polyethylene wax and zinc stearate gradually melt, volatilize and thermally decompose, and the organic phase inside the preform is continuously removed. In the sintering stage, the solid particles in the load-bearing reinforcing powder diffuse and combine at high temperature, forming sintering necks between particles and gradually densifying, finally forming a sintered part with an integral structure. This process essentially includes three continuous stages: injection molding, hot degreasing and high-temperature sintering, to obtain the integrated elevator component molding part.
[0081] Example 5
[0082] This embodiment provides an integrated processing and manufacturing process for elevator metal parts, including the following steps:
[0083] Step 1: Preparation of Stabilized Lubricating Powder
[0084] Weigh out 0.26 mL of γ-aminopropyltriethoxysilane, 90.0 mL of anhydrous ethanol, 25.0 mL of deionized water and 0.22 mL of glacial acetic acid and add them to the reaction vessel. Stir for 40 min to obtain the composite modified solution.
[0085] Weigh out 2.2g of hexagonal boron nitride, 2.2g of molybdenum disulfide, and 95.0mL of 18wt% hydrogen peroxide aqueous solution and add them to the reaction vessel. Stir until homogeneous, then heat the reaction vessel to 62℃ and stir for 2.5h. After filtering and collecting the solid, add the solid and 100.0mL of composite modification solution to the reaction vessel and heat the reaction vessel to 72℃ and stir for 3.5h. After the reaction is complete, filter and collect the filter cake. Wash the filter cake once with anhydrous ethanol and once with deionized water, then place it in a drying oven at 85℃ and vacuum dry for 10h. Finally, lightly pulverize and pass it through a 320-mesh sieve to obtain the stabilized lubricating powder.
[0086] Step 2: Preparation of integrated molding material for elevator components
[0087] By weight, 4.4 parts of paraffin wax, 2.4 parts of polyethylene wax and 1.2 parts of zinc stearate were weighed and added to a mixer, heated and melted, and stirred. After stirring evenly, 41 parts of the load-bearing strengthening powder prepared in Example 2 were added, and after stirring evenly, 4.4 parts of the stabilizing lubricating powder were added. The mixture was kneaded at 128°C for 45 minutes. After kneading, the material was poured out while hot and cooled to room temperature. Then, it was coarsely crushed and granulated to obtain an integrated molding material for elevator parts with a particle size of 3 mm.
[0088] Step 3: Fabrication of integrated molded elevator components
[0089] The integral molding material of elevator parts is added to the barrel of an injection molding machine and heated and plasticized at a temperature of 145℃ for 8 minutes, a mold temperature of 55℃, an injection pressure of 110MPa, and a holding time of 35 seconds. After uniform plasticization, it is injected into the mold cavity for molding. The elevator part blank is then demolded and placed in a degreasing furnace under a nitrogen atmosphere at a temperature of 3℃ / min to 420℃ and held for 4 hours for degreasing. Subsequently, it is placed in a sintering furnace under a vacuum of less than 10Pa, a temperature of 8℃ / min to 1150℃, and held for 2 hours for sintering. After sintering, it is cooled to room temperature, removed, and shaped and mechanically finished to obtain a rectangular plate with dimensions of 100mm×25mm×6mm. Two mounting holes with a diameter of Φ6.5mm and a center distance of 70mm are arranged along the length, and the end caps are rounded with R2.
[0090] Example 6
[0091] This embodiment provides an integrated processing and manufacturing process for elevator metal parts, including the following steps:
[0092] Step 1: Preparation of Stabilized Lubricating Powder
[0093] Weigh out 0.26 mL of γ-aminopropyltriethoxysilane, 90.0 mL of anhydrous ethanol, 25.0 mL of deionized water and 0.22 mL of glacial acetic acid and add them to the reaction vessel. Stir for 40 min to obtain the composite modified solution.
[0094] Weigh out 2.2g of hexagonal boron nitride, 2.2g of molybdenum disulfide, and 95.0mL of 18wt% hydrogen peroxide aqueous solution and add them to the reaction vessel. Stir until homogeneous, then heat the reaction vessel to 62℃ and stir for 2.5h. After filtering and collecting the solid, add the solid and 100.0mL of composite modification solution to the reaction vessel and heat the reaction vessel to 72℃ and stir for 3.5h. After the reaction is complete, filter and collect the filter cake. Wash the filter cake once with anhydrous ethanol and once with deionized water, then place it in a drying oven at 85℃ and vacuum dry for 10h. Finally, lightly pulverize and pass it through a 320-mesh sieve to obtain the stabilized lubricating powder.
[0095] Step 2: Preparation of integrated molding material for elevator components
[0096] By weight, 4.4 parts of paraffin wax, 2.4 parts of polyethylene wax and 1.2 parts of zinc stearate were weighed and added to a mixer, heated and melted, and stirred. After stirring evenly, 41 parts of the load-bearing strengthening powder obtained in Example 3 were added, and after stirring evenly, 4.4 parts of the stabilizing lubricating powder were added. The mixture was kneaded at 128°C for 45 minutes. After kneading, the material was poured out while hot and cooled to room temperature. Then, it was coarsely crushed and granulated to obtain an integrated molding material for elevator parts with a particle size of 3 mm.
[0097] Step 3: Fabrication of integrated molded elevator components
[0098] The integral molding material of elevator parts is added to the barrel of an injection molding machine and heated and plasticized at a temperature of 145℃ for 8 minutes, a mold temperature of 55℃, an injection pressure of 110MPa, and a holding time of 35 seconds. After uniform plasticization, it is injected into the mold cavity for molding. The elevator part blank is then demolded and placed in a degreasing furnace under a nitrogen atmosphere at a temperature of 3℃ / min to 420℃ and held for 4 hours for degreasing. Subsequently, it is placed in a sintering furnace under a vacuum of less than 10Pa, a temperature of 8℃ / min to 1150℃, and held for 2 hours for sintering. After sintering, it is cooled to room temperature, removed, and shaped and mechanically finished to obtain a rectangular plate with dimensions of 100mm×25mm×6mm. Two mounting holes with a diameter of Φ6.5mm and a center distance of 70mm are arranged along the length, and the end caps are rounded with R2.
[0099] Comparative Example 1
[0100] The difference between this comparative example and Example 6 is that the load-bearing strengthening powder used in step two is replaced by the synergistic coating powder in step ③ of the preparation process.
[0101] Comparative Example 2
[0102] The difference between this comparative example and Example 6 is that the composite modified liquid is omitted in step one, and the filtered solid is directly used in subsequent steps.
[0103] Comparative Example 3
[0104] The difference between this comparative example and Example 6 is that in step three, the load-bearing strengthening powder and the adhesion lubricating powder are pre-mixed and then added at once.
[0105] Performance testing:
[0106] All test specimens were integral molded elevator metal parts obtained in Examples 4-6 and Comparative Examples 1-3. The specimens were uniformly rectangular plates of 100mm×25mm×6mm, with two mounting holes arranged along the length direction. The hole diameter was Φ6.5mm, the center distance between the holes was 70mm, and the rounded corners at both ends were R2. After removing the gate, flash, and burrs, the test was conducted. No machining or polishing was performed on the mounting holes, the main test surface, or the outer contour. After sintering and cooling to room temperature, each specimen was placed at 23±2℃ and 50±5% relative humidity for 24 hours before testing. Unless otherwise specified, three parallel specimens were taken from each group, and the results were taken as the arithmetic mean.
[0107] The absolute deviation of the hole diameter |ΔD| and the absolute deviation of the hole center distance |ΔP| were measured in accordance with GB / T 3177-2009 "Geometric Specifications of Products (GPS) - Inspection of Dimensions of Smooth Workpieces". The test results are expressed as absolute deviation of the hole diameter |ΔD| and absolute deviation of the hole center distance |ΔP|, respectively, with the unit being mm.
[0108] The specific test parameters are as follows: A coordinate measuring machine is used for measurement, and the equipment indication error is no higher than ±0.005mm; A datum is established with the largest plane of the sample, B datum is established with one long side, and C datum is established with one end face; the two mounting holes of each sample are evaluated using the least squares fitted circle, and the arithmetic mean of the measured diameters of the two holes is taken as the measured value of the hole diameter of the sample. The absolute deviation of the hole diameter |ΔD| is calculated according to the absolute value of the difference between the measured hole diameter and the nominal hole diameter of 6.50mm; the hole center distance is evaluated using the distance between the centers of the fitted circles of the two mounting holes, and the absolute deviation of the hole center distance |ΔP| is calculated according to the absolute value of the difference between the measured hole center distance and the nominal center distance of 70.00mm; each sample is measured 3 times, and the average value is taken as the result of the sample.
[0109] Surface roughness Ra was determined in accordance with GB / T 40389-2021 "Determination of Surface Roughness of Sintered Metal Materials (excluding cemented carbide)" and the test results are expressed as surface roughness Ra, with units of μm.
[0110] The specific test parameters are as follows: A contact roughness tester is used, with a stylus tip radius of 5μm, a cutoff wavelength of λc=2.5mm, an evaluation length of 12.5mm, and a measurement speed of 0.5mm / s. The test area is fixed on the original sintered surface of the main plane of the sample. The test area is no less than 5mm from the outer edge of the sample, no less than 3mm from the edge of the mounting hole, and no less than 3mm from the rounded transition area. Five measurement trajectories are evenly selected within the effective area of each sample, and the arithmetic mean of the five contours is taken as the surface roughness result of the sample.
[0111] The sintering density ρs was determined according to GB / T 3850-2015 "Determination of Density of Dense Sintered Metallic Materials and Hard Alloys", and the test result is expressed as sintering density ρs, with units of g / cm³. 3 ;
[0112] The specific test parameters are as follows: the Archimedes method is used for determination according to the standard. The test medium is deionized water and the medium temperature is controlled at 23±2℃. Before the test, the sample surface is cleaned and dried at 105±5℃ for 1 hour and then cooled to room temperature. Each sample is measured once, and the arithmetic mean of 3 parallel samples is taken as the final result.
[0113] The flatness error F is measured in accordance with GB / T 11337-2004 "Flatness Error Detection", and the test result is expressed as flatness error F, with the unit being mm;
[0114] The specific test parameters are as follows: A coordinate measuring machine is used for measurement. The main plane of the sample is used as the test object. After deducting the mounting hole area, the rounded corner area and the range of 5mm from the edge, 25 measuring points are evenly arranged in a 5×5 pattern in the effective plane. The flatness error of the main plane is calculated according to the standard. The flatness error value of the sample is taken as the result of one measurement for each sample. The arithmetic mean of three parallel samples is taken as the final result.
[0115] See Table 1 for specific data;
[0116] Table 1 - Performance Test Data for Each Sample
[0117]
[0118] Data Analysis:
[0119] Comparative analysis of the data in Table 1 reveals that the absolute deviation of the hole diameter, the absolute deviation of the hole center distance, the surface roughness of the integrated elevator component prepared by this invention are 0.07 mm, 0.10 mm, 4.4 μm, and 7.10 g·cm³. -3 Meanwhile, the flatness error was 0.22mm, and all data were better than the comparative example, indicating that:
[0120] In Comparative Example 1, after the continuous load-bearing unit is not formed in the system, the internal constraint relationship on which the molding material depends during the plasticizing, injection, degreasing and sintering stages is weakened. There is a lack of stable support path between key parts, and local shrinkage is more likely to occur at different times. This difference is further transmitted to the hole edge, boundary and adjacent transition area, making it difficult to keep the geometric relationship synchronous. The micro-inhomogeneity formed in the early stage is also more likely to continue and be amplified in the subsequent heat treatment.
[0121] In Comparative Example 2, after the interface stabilization structure failed to be established, it was difficult for the layered components to form a uniform bond with the carrier phase and the binder system when they entered the system. The dispersion state during the mixing and plasticizing stages was more prone to fluctuation. This fluctuation would be transmitted to the particle migration and binder phase coating process near the surface, making it difficult for the flow area near the mold cavity surface to maintain continuity and consistency. Furthermore, it would affect the synergistic evolution of the surface and internal regions during the degreasing and sintering processes.
[0122] In Comparative Example 3, the lack of a layered, progressive construction sequence during the construction process makes it easier for the components to compete for dispersion in the molten bonding environment, making it difficult to form a stable transfer structure. Before the load-bearing particles and the binder phase have completed their initial coupling, the interface-modifying components simultaneously participate in the migration, altering the coating path and local flow state of the particle surfaces. This difference continues to propagate along the plasticizing, injection, debinding, and sintering processes, making it even more difficult to establish a smooth correspondence between different regions.
[0123] In conclusion, the final state of the molded part does not depend on the local changes of a single component or a single step, but is related to the continuous coordination between the structural composition of the reinforcing powder, the interface stabilization mode of the lubricating powder, and the construction sequence of the molding material. When any link is omitted or changed, the original particle transfer, interface evolution and thermal shrinkage response relationship within the system will be difficult to maintain. The local differences formed in the early stage will continue to be transmitted along the plasticizing, injection, degreasing and sintering processes, and further affect the overall structural state.
[0124] The above description is merely an example and illustration of the structure of the present invention. Those skilled in the art can make various modifications or additions to the specific embodiments described, or use similar methods to replace them, as long as they do not deviate from the structure of the invention or exceed the scope defined in the claims, all of which should fall within the protection scope of the present invention.
[0125] In the description of this specification, references to terms such as "an embodiment," "example," "specific example," etc., indicate that a specific feature, structure, material, or characteristic described in connection with that embodiment or example is included in at least one embodiment or example of the invention. In this specification, illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples.
[0126] The preferred embodiments of the present invention disclosed above are merely illustrative of the invention. These preferred embodiments do not exhaustively describe all details, nor do they limit the invention to specific implementations. Clearly, many modifications and variations can be made based on the content of this specification. This specification selects and specifically describes these embodiments to better explain the principles and practical applications of the invention, thereby enabling those skilled in the art to better understand and utilize the invention. The invention is limited only by the claims and their full scope and equivalents.
Claims
1. A process for integrated processing and manufacturing of elevator metal parts, characterized in that, Includes the following steps: S1. Weigh out 3.6-4.4 parts of paraffin wax, 1.8-2.4 parts of polyethylene wax and 0.9-1.2 parts of zinc stearate by weight, add them to a mixer, heat and melt them, and stir until uniform. Then add 37-41 parts of load-bearing strengthening powder, continue stirring until uniform, and then add 3.6-4.4 parts of stabilizing and lubricating powder. Knead the mixture at 118-128℃ for 35-45 minutes. After post-processing, the integrated molding material for elevator parts is obtained. S2. The integrated composite material of elevator parts is added to the barrel of the injection molding machine and heated and plasticized. After uniform plasticization, it is injected into the mold cavity for molding. The elevator parts blank is demolded to obtain the elevator parts blank. The elevator parts blank is then placed in a degreasing furnace for degreasing treatment, and then placed in a sintering furnace for sintering treatment. After sintering, it is cooled to room temperature, the sintered body is taken out, and it is shaped and mechanically finished to obtain the integrated molded part of elevator parts.
2. The integrated processing and manufacturing process for elevator metal parts according to claim 1, characterized in that, In step S2, the heating and plasticizing temperature is 125-145℃, the plasticizing time is 3-8 min, the mold temperature is 35-55℃, the injection pressure is 70-110 MPa, and the holding time is 15-35 s; the degreasing treatment conditions are to heat to 320-420℃ at 1-3℃ / min under a nitrogen atmosphere and hold for 2-4 h; the sintering treatment conditions are to heat to 1080-1150℃ at 4-8℃ / min under a vacuum of less than 10 Pa and hold for 1-2 h.
3. The integrated processing and manufacturing process for elevator metal parts according to claim 1, characterized in that, The method for preparing the load-bearing strengthening powder is as follows: iron-based pre-alloyed porous powder and synergistic coating powder are added to a mixer and mixed. After being mixed evenly, the mixture is pressed into a blank. The blank is then placed in a vacuum sintering furnace, and the vacuum is evacuated to below 10 Pa. The temperature is increased to 430-470℃ at 4-6℃ / min and held for 35-45 min. The temperature is then increased to 1000-1040℃ at 7-9℃ / min and held for 50-70 min. The load-bearing strengthening powder is obtained after post-treatment. The ratio of the amount of iron-based pre-alloyed porous powder to the synergistic coating powder is 32-38g:4.5-5.8g.
4. The integrated processing and manufacturing process for elevator metal parts according to claim 3, characterized in that, The preparation method of the iron-based pre-alloyed porous powder is as follows: Ferric nitrate nonahydrate, chromium nitrate nonahydrate, nickel nitrate hexahydrate, ammonium molybdate tetrahydrate, copper nitrate trihydrate, and deionized water are added to a reaction vessel and stirred until uniformly dissolved. Citric acid is then added and stirring continues for 20-40 minutes. Ethylene glycol is then added, and the reaction vessel is heated to 85-90℃ and stirred for 2-4 hours. The resulting material is then dried at 115-125℃ for 10-14 hours, then treated at 280-320℃ for 0.5-1.5 hours, followed by holding at 780-820℃ for 1.5-2.5 hours under a hydrogen atmosphere, and then at 1050-1100℃ for 0.8-1.5 hours under a nitrogen atmosphere. The final treatment yields the iron-based pre-alloyed porous powder.
5. The integrated processing and manufacturing process for elevator metal parts according to claim 4, characterized in that, The ratio of the amounts of ferric nitrate nonahydrate, chromium nitrate nonahydrate, nickel nitrate hexahydrate, ammonium molybdate tetrahydrate, copper nitrate trihydrate, deionized water, citric acid, and ethylene glycol is 185-230g:19-24g:6.2-7.8g:1.7-2.2g:3.5-4.5g:720-900mL:108-132g:48-62mL.
6. The integrated processing and manufacturing process for elevator metal parts according to claim 3, characterized in that, The preparation method of the enhanced coating powder is as follows: titanium dihydrogenide, boron carbide and 0.15-0.25 wt% of tris(hydroxymethyl)aminomethane aqueous solution are added to a reaction vessel and stirred. After stirring evenly, dopamine hydrochloride is added and the mixture is kept at 25-30℃ and stirred for 5-7 hours. Boric acid is then added, and the reaction vessel is heated to 42-48℃ and stirred for 1.5-2.5 hours. After the reaction is completed, the filter cake is collected by filtration. The filter cake is washed with deionized water 1-2 times and then placed in a drying oven at 55-65℃ for vacuum drying for 8-12 hours. It is then lightly pulverized and passed through a 180-220 mesh sieve to obtain the enhanced coating powder.
7. The integrated processing and manufacturing process for elevator metal parts according to claim 6, characterized in that, The ratio of titanium dihydrogen phosphate, boron carbide, 0.15-0.25 wt% aqueous solution of tris(hydroxymethyl)aminomethane, dopamine hydrochloride, and boric acid is 3.2-4.2 g: 1.2-1.6 g: 180-220 mL: 0.35-0.48 g: 0.16-0.24 g.
8. The integrated processing and manufacturing process for elevator metal parts according to claim 1, characterized in that, The method for preparing the stabilized lubricating powder is as follows: hexagonal boron nitride, molybdenum disulfide, and 12-18 wt% hydrogen peroxide aqueous solution are added to a reaction vessel and stirred. After stirring evenly, the reaction vessel is heated to 58-62℃ and stirred for 1.5-2.5 h. After filtering and collecting the solid, the solid and the composite modified liquid are added to the reaction vessel, and the reaction vessel is heated to 68-72℃ and stirred for 2.5-3.5 h. The stabilized lubricating powder is obtained after post-processing.
9. The integrated processing and manufacturing process for elevator metal parts according to claim 8, characterized in that, The ratio of the hexagonal boron nitride, molybdenum disulfide, 12-18 wt% hydrogen peroxide aqueous solution and the composite modified solution is 1.7-2.2 g: 1.7-2.2 g: 70-95 mL: 80-100 mL.
10. The integrated processing and manufacturing process for elevator metal parts according to claim 8, characterized in that, The composite modified liquid is prepared by adding γ-aminopropyltriethoxysilane, anhydrous ethanol, deionized water and glacial acetic acid into a reaction vessel and stirring for 30-40 min to obtain the composite modified liquid. The ratio of the amount of γ-aminopropyltriethoxysilane, anhydrous ethanol, deionized water and glacial acetic acid is 0.18-0.26 mL:70-90 mL:18-25 mL:0.12-0.22 mL.